2022
DOI: 10.1002/ccd.30062
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of optimal procedural result after transcatheter edge‐to‐edge mitral valve repair in secondary mitral regurgitation

Abstract: Background Procedural success after transcatheter edge‐to‐edge mitral valve repair (TEER) is defined as a reduction of mitral regurgitation (MR) degree to Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
(88 reference statements)
4
10
1
Order By: Relevance
“…The benefits of achieving a very low grade of rMR following MV‐TEER could be particularly evident in patients without severe LV dilation or right ventricular dysfunction 29 . Our finding is concordant with the results of the entire cohort of the GIOTTO registry, where an rMR <2+ was strongly associated with a reduction in 1‐year mortality (HR: 0.62 [95% CI: 0.46–0.84]; p = 0.002) 10,30 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The benefits of achieving a very low grade of rMR following MV‐TEER could be particularly evident in patients without severe LV dilation or right ventricular dysfunction 29 . Our finding is concordant with the results of the entire cohort of the GIOTTO registry, where an rMR <2+ was strongly associated with a reduction in 1‐year mortality (HR: 0.62 [95% CI: 0.46–0.84]; p = 0.002) 10,30 …”
Section: Discussionsupporting
confidence: 86%
“…29 Our finding is concordant with the results of the entire cohort of the GIOTTO registry, where an rMR <2+ was strongly associated with a reduction in 1-year mortality (HR: 0.62 [95% CI: 0.46-0.84]; p = 0.002). 10,30 According to our results, the risk of death or rehospitalization at 2 years was comparable between the two different MR etiologies (logrank: p = 0.850). On the other hand, in the entire cohort of the GIOTTO registry, patients with FMR showed significantly worse outcomes compared to those with DMR at both 1-and 2-year followups.…”
Section: Discussionsupporting
confidence: 52%
“…In SMR, optimal MR reduction is still debated. In the COAPT trial, no outcome difference was found between patients with residual MR grade 0/1+ and 2+, while in registry studies a positive impact of lower residual MR was observed [80][81][82] . In challenging cases, MR reduction should be balanced against the increase of the transmitral gradient (>5 mmHg), which has been associated with worse outcomes 83 .…”
Section: Mitral Valve Teermentioning
confidence: 92%
“…We also observed that a residual MR 2+ (vs. 0/1+) post‐M‐TEER was associated with an 87% reduced likelihood to have a TR ≤2+ at short‐term follow‐up. This confirms the importance to achieve optimal procedural result after M‐TEER in order to derive a prognostic benefit from the procedure 17–20 …”
Section: Discussionmentioning
confidence: 54%
“…This confirms the importance to achieve optimal procedural result after M-TEER in order to derive a prognostic benefit from the procedure. [17][18][19][20] There is only a single-centre study by Kavsur et al 10 assessing predictors of TR improvement after M-TEER by a multivariable model. This study showed that atrial fibrillation, tricuspid annulus dimensions ≥34 mm and residual MR ≥2+ were associated with a reduced probability to improve TR.…”
Section: Predictors Of Tricuspid Regurgitation Improvementmentioning
confidence: 99%